Preparation method of high-impact-resistance titanium dioxide special for polycarbonate
By beating and dispersing titanium dioxide, acidic inorganic envelope and organic envelope treatment, a special titanium dioxide product for polycarbonate with high impact resistance was prepared, which solved the problem of insufficient hydrolysis stability of titanium dioxide in polycarbonate and significantly improved its impact resistance.
Patent Information
- Application Number
- CN202510230914.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-25
AI Technical Summary
Most of the existing plastic general titanium dioxide products cannot meet the problem of insufficient hydrolysis resistance and stability of polycarbonate, and cannot meet the special needs of polycarbonate-specific titanium dioxide.
By beating and dispersing the titanium dioxide primary product, a titanium dioxide slurry is obtained, and the acid inorganic envelope and organic envelope are successively treated to form a polycarbonate special titanium dioxide product with high impact resistance.
It effectively improves the impact resistance of titanium dioxide in polycarbonate and solves the problem of insufficient hydrolysis stability of polycarbonate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium dioxide, in particular to a method for preparing titanium dioxide special for polycarbonate with high impact resistance. Background Art
[0002] Polycarbonate is a non-crystalline thermoplastic. Due to its advantages such as heat aging resistance, insulation performance, impact resistance, and light transmittance, it is widely used in building materials, automobile manufacturing, medical equipment, aerospace, electronics, optical lenses, packaging and other industries. At present, polycarbonate has become the fastest growing general engineering plastic among the five major engineering plastics. In 2017, the apparent demand for polycarbonate in my country was 1.727 million tons, and the output was 630,000 tons. In 2022, the apparent demand expanded to 2.875 million tons, and the output increased to 1.78 million tons, a year-on-year increase of 36.9% over the output in 2021. It can be seen that there is a large market space for the development of the polycarbonate industry. Titanium dioxide is a white pigment with excellent performance. It is widely used in coatings, plastics, papermaking and other fields. It is called "industrial MSG". Due to the special structure of polycarbonate (PC), there are problems such as insufficient hydrolysis stability and easy fading. There are special requirements for blended titanium dioxide, and most of the existing general titanium dioxide products for plastics cannot meet this demand. Titanium dioxide manufacturers have developed titanium dioxide for polycarbonate, such as Ishihara's PC-3, Connors' R2233, CITIC Titanium's CR-211, Yibin Tianyuan's TYR-569, etc. At present, the price of foreign titanium dioxide for polycarbonate is about 8,000 yuan / ton higher than that of domestic products, and domestic titanium dioxide products are still blank in the field of high-end titanium dioxide for polycarbonate.
[0003] CN 107722676 A discloses the use and method of modified polydimethylsiloxane as an organic treatment agent for titanium dioxide, and the method comprises the following steps: the titanium dioxide treated with inorganic coating is filtered, washed, and then mixed evenly with the modified polydimethylsiloxane, dried, and crushed; the mixing can be evenly carried out by conventional methods. The prior art discloses that titanium dioxide is treated organically with modified polydimethylsiloxane to obtain titanium dioxide having high temperature resistance, high dispersibility, and storage stability. However, the prior art does not disclose whether the inorganic coated titanium dioxide treated organically with modified polydimethylsiloxane is suitable for polycarbonate.
[0004] CN 111117297 B discloses a surface coating process for submicron high-purity titanium dioxide, which includes the following steps: step S1, adding the primary titanium dioxide to the deionized water of chitosan and dodecyl betaine to prepare a titanium dioxide base material; step S2, sequentially adding sodium hexametaphosphate and sodium silicate to the titanium dioxide base material to prepare a silicon-coated titanium dioxide slurry; step S3, adding sodium metaaluminate to the silicon-coated titanium dioxide slurry to prepare silicon-aluminum-coated titanium dioxide. The prior art introduces chitosan and cyclodextrin, improves the stability and firmness of the oxide film coated on the surface of titanium dioxide, and greatly improves the weather resistance, stability, brightness and acid solubility of titanium dioxide. However, before the chitosan in the prior art is coated on the surface of titanium dioxide, it is also subjected to a modified pretreatment of introducing carboxyl groups to improve the stability of the chitosan coating, and the dispersing effect of chitosan on titanium dioxide under an acidic pH regulator is not disclosed.
[0005] CN 107857899 B discloses a method for producing rutile titanium dioxide for plastics, which mainly comprises the following steps: (1) crushing and acid hydrolysis; (2) sedimentation: adding a flocculant to the titanium liquid B1 obtained in step (1); then removing solid impurities by multi-step filtration to obtain titanium liquid B2; (3) hydrolysis; (4) calcination; (5) wet grinding; (6) inorganic coating; (7) organic coating and air flow crushing: subjecting the material E1 obtained in step (6) to organic coating and air flow crushing to obtain the product; the flocculant in step (2) is selected from one or more of starch, chitosan, modified polyacrylamide and cellulose; the inorganic coating agent used in the inorganic coating in step (6) is an aluminum coating agent; the organic coating agent used in the organic coating in step (7) is selected from one or more of trimethylolethane, trimethylolpropane, silicone oil and silane. The prior art changes the process to produce titanium dioxide with high whiteness and brightness, which can meet the requirements for plastic use. However, the prior art does not disclose the dispersing effect of chitosan on titanium dioxide.
[0006] CN 114231054 A discloses titanium dioxide powder for polycarbonate and a preparation method thereof, comprising the following steps: (1) adding titanium tetrachloride, silicon tetrachloride and aluminum trichloride together into an oxidation furnace for oxidation to obtain a chlorinated primary product; (2) adding the chlorinated primary product obtained in step (1) together with organic matter into a granulation system for granulation to obtain a titanium dioxide powder for polycarbonate. This prior art uniformly coats a layer of organic matter on the surface of the chlorinated primary product, improves the compatibility of titanium dioxide powder with a polyurethane resin system, and enhances the dispersibility of titanium dioxide powder in a polyurethane resin system. However, this prior art does not involve the surface properties of titanium dioxide powder and the degradation of polycarbonate caused by moisture.
[0007] CN 107805321 A discloses a method for preparing a titanium dioxide pigment for polycarbonate, comprising the steps of beating a primary product of rutile titanium dioxide to prepare a titanium dioxide slurry, adjusting the pH value of the slurry to 9.0-11.0 with an inorganic alkali solution, adding a water-soluble silicate solution for aging, and then grinding the slurry; coating the ground slurry with a water-soluble silicate solution first, and then coating the slurry with a water-soluble alkaline aluminum salt solution, washing, drying, and steam-powdering to obtain a semi-finished product; modifying the semi-finished product after the steam-powdering with an organic surface modifier at room temperature, and then drying and crushing the treated slurry to obtain a titanium dioxide pigment for polycarbonate. The titanium dioxide pigment prepared by the prior art can have very good compatibility with polycarbonate, and can improve the mechanical properties and anti-aging properties of the product. However, the prior art does not involve the surface properties of titanium dioxide and the degradation of polycarbonate caused by moisture.
[0008] Based on this, there is room for improvement in the surface treatment of titanium dioxide. Summary of the invention
[0009] In view of this, the present invention provides a method for preparing titanium dioxide specially used for polycarbonate with high impact resistance, which solves the technical problem that most existing general-purpose titanium dioxide products for plastics cannot meet the special requirements of blended titanium dioxide powder due to the problem that the hydrolysis stability of polycarbonate is not high enough.
[0010] The invention provides a method for preparing titanium dioxide specially used for polycarbonate with high impact resistance, comprising: beating and dispersing a primary titanium dioxide product to obtain titanium dioxide slurry, and sequentially performing acidic inorganic coating and organic coating on the titanium dioxide slurry to obtain a titanium dioxide product specially used for polycarbonate with high impact resistance.
[0011] In some embodiments, slurrying and dispersing the primary titanium dioxide product to obtain titanium dioxide slurry includes: adding an acidic pH regulator, a dispersant and the primary titanium dioxide product into deionized water for slurrying and dispersing, adding zirconium beads, stirring and then sieving to obtain titanium dioxide slurry.
[0012] In some embodiments, the acidic pH regulator includes acetic acid; the dispersant includes chitosan, and the added amount of the dispersant is 0.05% to 0.4% of the initial quality of the titanium dioxide.
[0013] In some embodiments, the acidic inorganic coating of titanium dioxide slurry comprises the following steps: Step 1, preparing acid solution; Step 2, diluting the titanium dioxide slurry, heating the diluted titanium dioxide slurry to a first temperature and maintaining the temperature, to obtain a titanium dioxide slurry at a first temperature; Step 3, adding a sodium aluminate solution to the titanium dioxide slurry at the first temperature, and simultaneously adding the acid solution of step 1, controlling the pH of the titanium dioxide slurry at the first temperature to a first pH, adding for a first time, and aging for a second time to obtain an aged titanium dioxide slurry; Step 4, adjusting the pH of the aged titanium dioxide slurry to a second pH, adding the solution for a third time, and aging the solution for a fourth time to obtain an inorganic coated titanium dioxide slurry.
[0014] In some embodiments, in step 1, preparing the acid solution includes diluting the acid with deionized water to a first mass concentration, and the first mass concentration is 5% to 15%.
[0015] In some embodiments, in step 2, diluting the titanium dioxide slurry includes diluting the titanium dioxide slurry with deionized water to a second concentration, and the second concentration is 250 g / L to 400 g / L.
[0016] In some embodiments, in step 3, adding sodium aluminate solution to the titanium dioxide slurry at the first temperature includes: adding the sodium aluminate solution to the titanium dioxide slurry at the first temperature according to a first mass ratio of sodium aluminate to the initial titanium dioxide, the first mass ratio is 1.6% to 2.0%, the first pH is 4 to 6, the first time is 180 min to 240 min, and the second time is 60 min to 90 min.
[0017] In some embodiments, in step 4, adjusting the pH of the aged titanium dioxide slurry to a second pH includes: adjusting the pH of the aged titanium dioxide slurry to a second pH with an alkaline pH adjuster; the alkaline pH adjuster is one of a sodium hydroxide solution or a potassium hydroxide solution; the second pH is 6.0 to 7.0, the third time is 20 min to 40 min, and the fourth time is 60 min to 120 min.
[0018] In some embodiments, organic coating of titanium dioxide slurry includes: filtering, washing, drying and crushing the inorganic coated titanium dioxide slurry, adding an organic treatment agent to continue crushing, and then drying and air flow crushing to obtain a titanium dioxide product for polycarbonate with high impact resistance.
[0019] In some embodiments, the organic treating agent is a mixture of a hydroxy-modified silicone oil containing an alkyl group and di(2-ethylhexyl) phthalate.
[0020] Beneficial effects of the present invention: The method for preparing titanium dioxide specially used for polycarbonate with high impact resistance of the present invention can effectively improve the impact resistance of titanium dioxide in polycarbonate by optimizing and adjusting the surface treatment process (inorganic coating and organic coating). DETAILED DESCRIPTION
[0021] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with specific embodiments.
[0022] It should be noted that all expressions using "first" and "second" in the embodiments of the present invention are for distinguishing two non-identical entities with the same name or non-identical parameters. It can be seen that "first" and "second" are only for the convenience of expression and should not be understood as limitations on the embodiments of the present invention. The subsequent embodiments will not explain this one by one.
[0023] The method for preparing titanium dioxide for polycarbonate with high impact resistance of the present invention comprises: beating and dispersing titanium dioxide primary product to obtain titanium dioxide slurry, and sequentially performing acid inorganic coating and organic coating on the titanium dioxide slurry to obtain titanium dioxide product for polycarbonate with high impact resistance.
[0024] In some embodiments, slurrying and dispersing the primary titanium dioxide product to obtain titanium dioxide slurry includes: adding an acidic pH regulator, a dispersant and the primary titanium dioxide product into deionized water for slurrying and dispersing, adding zirconium beads, stirring and then sieving to obtain titanium dioxide slurry.
[0025] In some embodiments, the primary titanium dioxide product refers to an intermediate product that has undergone preliminary processing during the titanium dioxide production process but has not yet reached the quality standards of the final product.
[0026] In some embodiments, the acidic pH regulator includes acetic acid; the dispersant includes chitosan, and the added amount of the dispersant is 0.05% to 0.4% of the initial quality of the titanium dioxide.
[0027] Chitosan is a high molecular polymer with steric hindrance. Chitosan can form an adsorption layer on the surface of titanium dioxide particles. When titanium dioxide particles are close to each other, the adsorption layer produces steric hindrance, preventing titanium dioxide particles from agglomerating, and making titanium dioxide uniformly dispersed in the system. Chitosan has an electrostatic stabilizing effect. There are functional groups such as amino groups on the chitosan molecular chain. Under certain conditions, it will be protonated and positively charged. It will combine with negatively charged titanium dioxide particles through electrostatic action, increase the surface charge density of titanium dioxide particles, enhance electrostatic repulsion, and improve dispersion stability. Chitosan has a chelating effect. The amino and hydroxyl groups of chitosan can form chelates with metal ions in titanium dioxide, reduce particle agglomeration caused by metal ions, and reduce the concentration of impurity ions in the system, thereby improving the dispersion effect. Chitosan can adjust the viscosity and rheology of the titanium dioxide dispersion system, so that the titanium dioxide dispersion system has good fluidity and stability, and prevent particles from settling and agglomerating due to gravity.
[0028] Acetic acid promotes the dissolution of chitosan. There are a large number of hydrogen bonds between chitosan molecules, which are difficult to dissolve in water. Acetic acid can react with the amino groups in the chitosan molecules to protonate, so that the chitosan molecular chain carries a positive charge, and the hydrogen bonds between the molecules are destroyed, so that it is easily soluble in water to form a uniform solution, so that it can play a dispersing role on titanium dioxide. Acetic acid can adjust the pH value of the system so that the surface of titanium dioxide carries a certain charge. At the same time, the protonation degree of chitosan increases under acidic conditions, and it carries more positive charges. The interaction between the two charges enhances the electrostatic repulsion between titanium dioxide particles, effectively preventing particle agglomeration and improving the dispersion effect. Acetic acid reduces the surface tension of the liquid, making titanium dioxide particles easier to wet. The hydrophilic groups on the chitosan molecular chain also help to improve the wettability of titanium dioxide. The synergistic effect of the two enables titanium dioxide particles to be better wetted by the dispersion medium, which is conducive to the adsorption of chitosan on its surface, and further enhances the dispersion stability. Acetic acid can react with some impurities such as metal ions in the titanium dioxide dispersion system, and play a certain chelating role. Chitosan also has a chelating effect. The two together reduce the adverse effects of impurity ions on the dispersion of titanium dioxide, reduce the risk of particle agglomeration caused by impurity ions, and make the dispersion effect of chitosan on titanium dioxide more stable.
[0029] In some embodiments, the stirring speed is controlled to be 3000 r / min to 4000 r / min.
[0030] In some embodiments, the screen is a 500 mesh screen.
[0031] In some embodiments, the titanium dioxide slurry has a first concentration, and the first concentration is controlled to be greater than or equal to 450 g / L.
[0032] In some embodiments, the acidic inorganic coating of titanium dioxide slurry comprises the following steps: Step 1, preparing acid solution; Step 2, diluting the titanium dioxide slurry, heating the diluted titanium dioxide slurry to a first temperature and maintaining the temperature, to obtain a titanium dioxide slurry at a first temperature; Step 3, adding a sodium aluminate solution to the titanium dioxide slurry at the first temperature, and simultaneously adding the acid solution of step 1, controlling the pH of the titanium dioxide slurry at the first temperature to a first pH, adding for a first time, and aging for a second time to obtain an aged titanium dioxide slurry; Step 4, adjusting the pH of the aged titanium dioxide slurry to a second pH, adding the solution for a third time, and aging the solution for a fourth time to obtain an inorganic coated titanium dioxide slurry.
[0033] In some embodiments, in step 1, preparing the acid solution includes diluting the acid to a first mass concentration with deionized water. For example, the acid is analytical grade hydrochloric acid.
[0034] In some embodiments, the first mass concentration is 5% to 15%, that is, the mass of hydrogen chloride (HCl) accounts for 5% to 15% of the total mass of the acid solution.
[0035] In some embodiments, in step 2, diluting the titanium dioxide slurry includes diluting the titanium dioxide slurry to a second concentration with deionized water.
[0036] In some embodiments, the second concentration is 250 g / L to 400 g / L.
[0037] In some embodiments, the first temperature is 70°C to 90°C.
[0038] In some embodiments, in step 3, adding sodium aluminate solution to the titanium dioxide slurry at the first temperature includes: adding the sodium aluminate solution to the titanium dioxide slurry at the first temperature according to a first mass ratio of sodium aluminate to titanium dioxide.
[0039] In some embodiments, the first mass ratio is 1.6% to 2.0%.
[0040] In some embodiments, in step 3, the first pH is 4-6, the first time is 180 min-240 min, and the second time is 60 min-90 min.
[0041] In some embodiments, the mass concentration of the sodium aluminate solution is 95 g / L to 105 g / L in terms of aluminum oxide.
[0042] In some embodiments, in step 4, adjusting the pH of the aged titanium dioxide slurry to the second pH includes: adjusting the pH of the aged titanium dioxide slurry to the second pH using an alkaline pH adjuster.
[0043] In some embodiments, the second pH is 6.0-7.0, the third time is 20 min-40 min, and the fourth time is 60 min-120 min.
[0044] In some embodiments, the alkaline pH adjuster is one of a sodium hydroxide solution or a potassium hydroxide solution.
[0045] In some embodiments, organic coating of titanium dioxide slurry includes: filtering, washing, drying and crushing the inorganic coated titanium dioxide slurry, adding an organic treatment agent to continue crushing, and then drying and air flow crushing to obtain a titanium dioxide product for polycarbonate with high impact resistance.
[0046] In some embodiments, the organic treatment agent is a mixture of an organic silicon compound and an ester compound. The amount of the organic treatment agent added is 2% to 5% of the initial quality of the titanium dioxide.
[0047] Organic silicon compounds can reduce the surface energy between titanium dioxide particles, reduce the agglomeration of particles, make it easier to disperse evenly in coatings, plastics and other systems, and improve the performance and quality of products. Organic silicon has good UV resistance and oxidation resistance, which can effectively block the erosion of titanium dioxide by ultraviolet rays, oxygen and moisture in the external environment, improve the weather resistance of titanium dioxide, and prevent it from yellowing and powdering during use. Organic silicon compounds change the surface of titanium dioxide from hydrophilic to lipophilic, improve its compatibility and affinity with organic polymer materials, and can better combine with the matrix material in composite materials, improving the mechanical properties and comprehensive properties of the material.
[0048] Ester compound coating can reduce the surface energy between titanium dioxide particles, reduce particle agglomeration, make it disperse more evenly in the matrix of coatings, plastics, etc., and improve the optical and mechanical properties of the material. The ester compound coating can block ultraviolet rays, moisture and oxygen from contacting titanium dioxide, slow down the photocatalytic degradation and aging process of titanium dioxide, and improve the weather resistance and service life of the material. Ester compounds can improve the compatibility of titanium dioxide with organic matrices, make titanium dioxide and the matrix more closely combined, and improve the comprehensive performance of composite materials. For example, in plastics, it can improve the toughness and processing performance of products.
[0049] In some embodiments, the organosilicon compound includes a hydroxyl-modified silicone oil containing an alkyl group.
[0050] In some embodiments, the ester compound includes di(2-ethylhexyl)phthalate.
[0051] In some embodiments, the organic treatment agent is a mixture of hydroxy-modified silicone oil containing an alkyl group and di(2-ethylhexyl)phthalate, wherein the mass ratio of the hydroxy-modified silicone oil containing an alkyl group to di(2-ethylhexyl)phthalate is 4:1 to 19:1.
[0052] Compared with the prior art, the preparation method of polycarbonate-specific titanium dioxide with high impact resistance of the present invention adopts acetic acid as an acidic pH regulator and chitosan as a dispersant for acid pulping, and the hydroxyl groups of chitosan interact with the titanium dioxide particles so that the chitosan is adsorbed on the surface of the titanium dioxide particles, and the sugar ring structure of the chitosan provides a steric hindrance effect for the titanium dioxide particles. At the same time, under acidic conditions, the protonated amino groups of the chitosan provide an electrostatic repulsion effect for the titanium dioxide particles. These effects ensure the dispersion effect of titanium dioxide, which is conducive to the uniformity of subsequent inorganic coating; the inorganic coating adopts acidic aluminum coating to form amorphous aluminum hydroxide. Compared with crystalline aluminum hydroxide, disordered amorphous aluminum hydroxide can reduce the escape of electrons and reduce the degradation of polycarbonate. At the same time, by controlling the amount of aluminum coating, aluminum coating time and aging temperature, a dense and uniform amorphous titanium aluminum oxide is coated on the surface of titanium dioxide, and the crystal water content is small, which further reduces the degradation of polycarbonate; the organic coating adopts hydroxyl modified silicone oil containing alkyl, and the addition amount is large. Di (2-ethylhexyl) phthalate and alkyl ensure the dispersibility of titanium dioxide particles in the polycarbonate system through the principle of similar dissolution. At the same time, di (2-ethylhexyl) phthalate can react with polycarbonate through ester exchange reaction to play the role of crosslinking agent, dissipate energy in the process of polymer fracture, and play a role in enhancing impact resistance. The hydroxyl group provides a reaction site with titanium dioxide particles for the modified silicone oil, so that the organic treatment agent is closely connected with the surface of titanium dioxide. A larger amount of organic treatment agent added ensures that the organic treatment agent is coated on the surface of titanium dioxide, which can effectively prevent the titanium dioxide from adsorbing water and volatilizing the internal crystal water during storage.
[0053] Example 1 Acetic acid, chitosan and titanium dioxide pre-product with pH=4 were added to deionized water for pulping and dispersion. The amount of chitosan added was 0.2% of the quality of the titanium dioxide pre-product. Zirconium beads were added and stirred at a stirring speed of 3500 r / min and then passed through a 500-mesh sieve to obtain titanium dioxide slurry. The first concentration of the titanium dioxide slurry was 480 g / L. Analytical pure hydrochloric acid was diluted with deionized water to a first mass concentration of 5% dilute hydrochloric acid. The titanium dioxide slurry was diluted with deionized water to a second concentration of 300 g / L, and the diluted titanium dioxide slurry was heated to 80°C and maintained. According to the mass ratio of sodium aluminate to titanium dioxide pre-product of 1.8%, the sodium aluminate solution was added dropwise to the 80°C titanium dioxide slurry, and dilute hydrochloric acid was added dropwise at the same time. The pH of the 80°C titanium dioxide slurry was controlled to 5, and the addition was carried out for 180 min and matured for 60 min to obtain the matured titanium dioxide slurry. The pH of the matured titanium dioxide slurry is adjusted to 6.3-6.7 with sodium hydroxide solution, and then dripped for 20 minutes and matured for 60 minutes to obtain an inorganic coated titanium dioxide slurry. After the inorganic coated titanium dioxide slurry is filtered, washed, dried and crushed, an organic treatment agent including alkyl-containing hydroxy-modified silicone oil and di(2-ethylhexyl)phthalate is added and continued to be crushed. The amount of the organic treatment agent added is 3% of the initial quality of the titanium dioxide, and the mass ratio of the alkyl-containing hydroxy-modified silicone oil to di(2-ethylhexyl)phthalate is 9:1. Then, it is dried and air flow crushed to obtain a titanium dioxide product for polycarbonate.
[0054] Comparative Example 1 Acetic acid, chitosan and titanium dioxide pre-product with pH=4 were added to deionized water for pulping and dispersion. The amount of chitosan added was 0.2% of the quality of the titanium dioxide pre-product. Zirconium beads were added and stirred at a stirring speed of 3500 r / min and then passed through a 500-mesh sieve to obtain titanium dioxide slurry. The first concentration of the titanium dioxide slurry was 480 g / L. Analytical pure hydrochloric acid was diluted with deionized water to a first mass concentration of 5% dilute hydrochloric acid. The titanium dioxide slurry was diluted with deionized water to a second concentration of 300 g / L, and the diluted titanium dioxide slurry was heated to 80°C and maintained. According to the mass ratio of sodium aluminate to titanium dioxide pre-product of 1.8%, the sodium aluminate solution was added dropwise to the 80°C titanium dioxide slurry, and dilute hydrochloric acid was added dropwise at the same time. The pH of the 80°C titanium dioxide slurry was controlled to 5, and the addition was carried out for 180 min and matured for 60 min to obtain the matured titanium dioxide slurry. The pH of the matured titanium dioxide slurry is adjusted to 6.3-6.7 with sodium hydroxide solution, and the solution is added dropwise for 20 minutes and matured for 60 minutes to obtain an inorganic coated titanium dioxide slurry. The inorganic coated titanium dioxide slurry is filtered, washed, dried and crushed, and then dimethyl silicone oil is added to continue crushing, and the amount of dimethyl silicone oil added is 3% of the initial quality of the titanium dioxide, and then dried and air flow crushed to obtain the first titanium dioxide product.
[0055] Comparative Example 2 Add sodium hydroxide solution with pH=11, sodium silicate and titanium dioxide primary product to deionized water for pulping and dispersion. The amount of sodium silicate added is 0.2% of the initial quality of titanium dioxide. Add zirconium beads and stir at a stirring speed of 3500 r / min, then pass through a 500-mesh sieve to obtain titanium dioxide slurry. The first concentration of titanium dioxide slurry is 480g / L. Dilute analytical pure hydrochloric acid with deionized water to a first mass concentration of 5% dilute hydrochloric acid. Dilute the titanium dioxide slurry with deionized water to a second concentration of 300 g / L, and heat the diluted titanium dioxide slurry to 80°C and maintain. According to the mass ratio of sodium aluminate to titanium dioxide primary product of 1.8%, add sodium aluminate solution dropwise to the 80°C titanium dioxide slurry, and add dilute hydrochloric acid at the same time. The pH of the 80°C titanium dioxide slurry is controlled to 9, and the addition is 180 min. Ripening for 60 min, the slurry after aging is obtained. The pH of the matured titanium dioxide slurry is adjusted to 6.3-6.7 with sodium hydroxide solution, and the solution is added dropwise for 20 minutes and matured for 60 minutes to obtain an inorganic coated titanium dioxide slurry. After the inorganic coated titanium dioxide slurry is filtered, washed, dried and crushed, an organic treatment agent including alkyl-containing hydroxy-modified silicone oil and di(2-ethylhexyl)phthalate is added and crushed continuously, the amount of the organic treatment agent added is 3% of the initial quality of the titanium dioxide, and the mass ratio of the alkyl-containing hydroxy-modified silicone oil to di(2-ethylhexyl)phthalate is 19:1, and then dried and air flow crushed to obtain a second titanium dioxide product.
[0056] Comparative Example 3 Acetic acid, chitosan and titanium dioxide pre-product with pH=4 were added to deionized water for pulping and dispersion. The amount of chitosan added was 0.2% of the quality of the titanium dioxide pre-product. Zirconium beads were added and stirred at a stirring speed of 3500 r / min and then passed through a 500-mesh sieve to obtain titanium dioxide slurry. The first concentration of the titanium dioxide slurry was 480 g / L. Analytical pure hydrochloric acid was diluted with deionized water to a first mass concentration of 5% dilute hydrochloric acid. The titanium dioxide slurry was diluted with deionized water to a second concentration of 300 g / L, and the diluted titanium dioxide slurry was heated to 80°C and maintained. According to the mass ratio of sodium aluminate to titanium dioxide pre-product of 1.2%, the sodium aluminate solution was added dropwise to the 80°C titanium dioxide slurry, and dilute hydrochloric acid was added dropwise at the same time. The pH of the 80°C titanium dioxide slurry was controlled to 5, and the addition was carried out for 120 min and matured for 60 min to obtain the matured titanium dioxide slurry. The pH of the matured titanium dioxide slurry is adjusted to 6.3-6.7 with sodium hydroxide solution, and the solution is added dropwise for 20 minutes and matured for 60 minutes to obtain an inorganic coated titanium dioxide slurry. The inorganic coated titanium dioxide slurry is filtered, washed, dried and crushed, and then dimethyl silicone oil is added to continue crushing. The amount of dimethyl silicone oil added is 3% of the initial quality of the titanium dioxide, and then dried and air flow crushed to obtain a third titanium dioxide product.
[0057] Example 1 and Comparative Examples 1-3 use the same mass of primary titanium dioxide powder, which is titanium dioxide particles obtained by oxidation reaction of titanium tetrachloride.
[0058] The titanium dioxide product for polycarbonate of Example 1, the first titanium dioxide product of Comparative Example 1, the second titanium dioxide product of Comparative Example 2, and the third titanium dioxide product of Comparative Example 3 were blended with polycarbonate and pelletized to prepare respective samples. The samples were dissolved and filtered with tetrahydrofuran (THF) and then subjected to gel permeation chromatography (GPC) test. The samples were also tested for impact resistance. The results are shown in Table 1.
[0059] Table 1 Molecular weight and impact resistance test results of samples
[0060] The impact resistance index of polycarbonate used in the titanium dioxide product for polycarbonate prepared by the method for preparing titanium dioxide for polycarbonate with high impact resistance of the present invention is better than the impact resistance index of polycarbonate used in the titanium dioxide products of Comparative Examples 1 to 3.
[0061] The method for preparing titanium dioxide specially used for polycarbonate with high impact resistance of the present invention can effectively improve the impact resistance of titanium dioxide in polycarbonate by optimizing and adjusting the surface treatment process (inorganic coating and organic coating).
[0062] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0063] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for preparing titanium dioxide for polycarbonate with high impact resistance, characterized in that: include: The titanium dioxide primary product is pulped and dispersed to obtain titanium dioxide slurry, and the titanium dioxide slurry is sequentially subjected to acid inorganic coating and organic coating to obtain a titanium dioxide product specially used for polycarbonate with high impact resistance.
2. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 1, characterized in that: The method of beating and dispersing the primary titanium dioxide product to obtain the titanium dioxide slurry includes: adding an acidic pH regulator, a dispersant and the primary titanium dioxide product into deionized water for beating and dispersing, adding zirconium beads for stirring and then sieving to obtain the titanium dioxide slurry.
3. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 2, characterized in that: The acidic pH regulator includes acetic acid; the dispersant includes chitosan, and the added amount of the dispersant is 0.05% to 0.4% of the initial quality of the titanium dioxide.
4. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 1, characterized in that: The method of subjecting the titanium dioxide slurry to an acidic inorganic coating comprises the following steps: Step 1, preparing acid solution; Step 2, diluting the titanium dioxide slurry, heating the diluted titanium dioxide slurry to a first temperature and maintaining the temperature to obtain a titanium dioxide slurry at a first temperature; Step 3, adding a sodium aluminate solution to the titanium dioxide slurry at the first temperature, and simultaneously adding the acid solution in step 1, controlling the pH of the titanium dioxide slurry at the first temperature to a first pH, adding for a first time, and aging for a second time to obtain an aged titanium dioxide slurry; Step 4, adjusting the pH of the aged titanium dioxide slurry to a second pH, adding the solution for a third time, and aging the solution for a fourth time to obtain an inorganic coated titanium dioxide slurry.
5. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 4, characterized in that: In the step 1, preparing the acid solution includes diluting the acid with deionized water to a first mass concentration, wherein the first mass concentration is 5% to 15%.
6. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 4, characterized in that: In the step 2, diluting the titanium dioxide slurry includes diluting the titanium dioxide slurry with deionized water to a second concentration, wherein the second concentration is 250 g / L to 400 g / L.
7. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 4, characterized in that: In the step 3, adding the sodium aluminate solution to the titanium dioxide slurry at the first temperature includes: adding the sodium aluminate solution to the titanium dioxide slurry at the first temperature according to a first mass ratio of sodium aluminate to titanium dioxide, the first mass ratio is 1.6% to 2.0%, the first pH is 4 to 6, the first time is 180 minutes to 240 minutes, and the second time is 60 minutes to 90 minutes.
8. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 4, characterized in that: In step 4, adjusting the pH of the aged titanium dioxide slurry to a second pH includes: adjusting the pH of the aged titanium dioxide slurry to the second pH with an alkaline pH adjuster; the alkaline pH adjuster is one of a sodium hydroxide solution or a potassium hydroxide solution; the second pH is 6.0 to 7.0, the third time is 20 minutes to 40 minutes, and the fourth time is 60 minutes to 120 minutes.
9. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 4, characterized in that: The organic coating of the titanium dioxide slurry includes: filtering, washing, drying and crushing the inorganic coated titanium dioxide slurry, adding an organic treatment agent to continue crushing, and then drying and air flow crushing to obtain a polycarbonate-specific titanium dioxide product with high impact resistance.
10. The method for preparing titanium dioxide for polycarbonate with high impact resistance according to claim 9, characterized in that: The organic treatment agent is a mixture of hydroxy-modified silicone oil containing an alkyl group and di(2-ethylhexyl) phthalate.
Citation Information
Patent Citations
Application of modified polydimethylsiloxane serving as titanium dioxide organic treatment agent and method
CN107722676A
Preparation method of special titanium dioxide pigment for polycarbonate
CN107805321A
A kind of production method of rutile type titanium dioxide special for plastics
CN107857899B
Surface coating process of submicron high-purity titanium dioxide
CN111117297B